1996
DOI: 10.1046/j.1471-4159.1996.67052134.x
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Retrograde Transport of Cholera Toxin from the Plasma Membrane to the Golgi Apparatus and Endoplasmic Reticulum Decreases During Neuronal Development

Abstract: Various glycolipid-binding toxins are internalized from the cell surface to the Golgi apparatus. Prominent among these is cholera toxin (CT), which consists of a pentameric B subunit that binds to ganglioside GM1 and an A subunit that mediates toxicity. We now demonstrate that rhodamine (Rh)-CT can be further internalized from the Golgi apparatus to the endoplasmic reticulum (ER) in cultured hippocampal neurons and in neuroblastoma N18TG-2 cells and that the A subunit is essential for retrograde transport to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Endocytosis from selected regions of the plasma membrane would then result in the formation of endosomes in which the overall concentration of a given analogue did not match its concentration in the plasma membrane. It is interesting that a previous study using cholera toxin to monitor the internalization of GM1 ganglioside found that the rate of internalization of this marker was decreased significantly during maturation of hippocampal neurons (Sofer and Futerman, 1996). Although the current study used different methodology and cell types, our findings lead us to speculate that reduced internalization of certain cell‐surface lipids may be an important principle to consider in future studies of neuronal cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis from selected regions of the plasma membrane would then result in the formation of endosomes in which the overall concentration of a given analogue did not match its concentration in the plasma membrane. It is interesting that a previous study using cholera toxin to monitor the internalization of GM1 ganglioside found that the rate of internalization of this marker was decreased significantly during maturation of hippocampal neurons (Sofer and Futerman, 1996). Although the current study used different methodology and cell types, our findings lead us to speculate that reduced internalization of certain cell‐surface lipids may be an important principle to consider in future studies of neuronal cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…GM1 resides in caveolae (Parton, 1994). Cholera toxin is internalized from the plasma membrane primarily, but possibly not exclusively, via caveolae (Mukherjee et al, 1997;Shogomori and Futerman, 2001;Pelkmans and Helenius, 2002) and then reaches the Golgi system (Sofer and Futerman, 1996;Pelkmans and Helenius, 2002). Because GM1 also associates with Trk receptors, it has been speculated that cholera toxin may bind (and be trafficked) in a GM1-Trk-p75 complex .…”
Section: Cholera Toxinmentioning
confidence: 99%
“…Consistent with this notion, those internalized proteins that are most efficiently routed to an anterograde axonal pathway pass through the Golgi apparatus. These proteins include anterogradely transcytosed proteins such as lectins (WGA, Broadwell and Balin, 1985), cholera toxin (Sofer and Futerman, 1996;Shogomori and Futerman, 2001), tetanus toxin (Schwab and Thoenen, 1977a), as well as trophic factors . Internalized proteins that do not travel anterogradely or do so less efficiently, on the other hand, do not seem to be routed through the Golgi system (Claude et al, 1982;Butowt and von Bartheld, 2001).…”
Section: Pathways: Sortingmentioning
confidence: 99%
“…1987). From here, unlike molecules that are recycled back to the cell surface, or transported directly to lysosomes for degradation, CT is transported to the Golgi apparatus and then to the endoplasmic reticulum (Sofer and Futerman 1995, 1996). cAMP is generated (Orlandi et al .…”
mentioning
confidence: 99%